To Determine the Prevalence, Diagnosis, and Treatment of Cholelithiasis among the age of 20-60 years - Muhammad Zohaib Hassan, Yasir Arfat, Zahid Iqbal, Saad Khan, Muhammad Imran Khokhar, Faisal Shabbir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cholelithiasis is a common hepatobiliary disorder with significant clinical and surgical implications. Despite its high prevalence worldwide, data regarding its burden among adults in the economically productive age group remain limited in many developing regions. Objective: To determine the prevalence of cholelithiasis among adults aged 20–60 years and to assess its distribution according to demographic and anthropometric factors. Methods: A hospital-based cross-sectional study was conducted in the Department of Radiology, Gujranwala Teaching Hospital, from August 2021 to February 2022. A total of 2000 adults aged 20–60 years undergoing abdominal ultrasonography were enrolled using consecutive sampling. Demographic data, body mass index, and family history were recorded. Cholelithiasis was defined as the ultrasonographic presence of gallstones. Data were analyzed using SPSS, and results were expressed as frequencies, percentages, and mean ± standard deviation. Results: Among the 2000 participants, 53% were females and 47% were males. The overall prevalence of cholelithiasis was 5%. Gallstones were more frequently observed in females compared to males. A higher prevalence was noted in younger adults compared to older participants within the studied age range. Increased body mass index was associated with a higher frequency of gallstone disease. Conclusion: Cholelithiasis was present in a considerable proportion of adults aged 20–60 years, with higher prevalence among females and individuals with increased body mass index. These findings highlight the importance of early identification of at-risk individuals and the role of lifestyle modification in reducing the burden of gallstone disease. Keywords: Cholelithiasis; Gallstone disease; Prevalence; Ultrasonography; Body mass index.